SEMANTIC APPROACHES IN KNOWLEDGE MANAGEMENT: A SYSTEMATIC LITERATURE REVIEW - Widuri Sri MP, Rinda (Universitas Negeri Surabaya, 2025)
Knowledge management has become a key focus in modern organizational strategies to maintain competitive advantage and encourage innovation. Semantic technologies, including ontologies, semantic annotations, and natural language processing techniques, offer great potential to improve knowledge management by providing a framework that enables better data integration and increases the interoperability of information systems. This research conducted a Systematic Literature Review (SLR) to evaluate the benefits, challenges, and best practices in applying semantic technology in knowledge management. Key findings show that semantic technology can improve operational efficiency, decision-making quality, and collaboration between teams. However, challenges such as the complexity of ontology development and maintenance as well as integration with existing systems require special attention. This research also provides recommendations for phased implementation, employee training, and use of integrated platforms to overcome these challenges and maximize the benefits of semantic technology in organizational knowledge management.